Geomorphological Mapping of Allahabad District, Uttar Pradesh - Chaturvedi, Richa (National Geographical Journal of India, 2022)
In this paper an attempt has been made to study the mapping of the geomorphological landform. The geomorphological mapping was carried out with the help of IRS (LISS III) imagery by visual interpretation technique.In India remote sensing has been used for various applications during the last four decades and has contributed significantly towards development. Identification of landforms using key interpretation features such as image tone, texture, association and terrain shadow has been done in this paper. Based on the existing landforms, drainage characteristics on the imagery, various geomorphic units have been identified in district Allahabad.